High diagnostic accuracy of inguinal ultrasonography and fine‐needle aspiration followed by dynamic sentinel lymph node biopsy in men with impalpable and palpable inguinal lymph nodes. (5th March 2022) - Lee, Esther W.C.; Issa, Allaudin; Oliveira, Pedro; Lau, Maurice; Sangar, Vijay; Parnham, Arie; Fankhauser, Christian D.
Abstract : Objectives: To assess the accuracy of dynamic sentinel lymph node biopsy (DSNB) after negative ultrasonography (US) guided fine‐needle aspiration (FNA) for inguinal lymph node (ILN) staging. Patients and Methods: We performed a retrospective analysis of men with ≥T1G2 penile cancer and negative inguinal US‐guided FNA undergoing DSNB. Men with suspicious US but negative FNA underwent US‐guided ILN excision. Men with ≥T1G2 local recurrence during follow‐up and non‐squamous cell histologies were excluded. Descriptive analysis was performed, and sensitivity and negative predictive values (NPVs) were calculated. Results: We included 403 men with 728 groins with negative FNA undergoing DSNB ± US‐guided LN excision. At least one sentinel LN (SN) was visualised in 93% during the first and in 7% during the second lymphoscintigraphy. The median SNs visualised preoperatively was 1 SN and a median of 2 LNs were resected. ILN metastases were detected in 9% groins in men with impalpable and in 17% men with palpable LNs. Stratified by impalpable and palpable ILN, non‐local recurrence despite pathologically negative DSNBs was seen in 0.5% and 0%, respectively. Limited to men with ≥24 months follow‐up, non‐local recurrence after negative DSNBs was seen in 0.4% and 0%, respectively. The sensitivity of DSNB was 96% and the NPV was 100%. The main limitation of this analysis is its retrospective nature with inherit biases. Conclusions: Inguinal US and FNA followed by DSNB can accurately stage men with both impalpable and palpable ILN, which provides logistical and surgical advantages.